Increased expression of chaperone proteins in response to DENV 2 infection of Huh-7 liver cells. - Chanida Chumchanchira; Wannapa Sornjai; Sittiruk Roytrakul; Pathrapol Lithanatudom; Duncan R Smith (PLoS ONE)
The mosquito transmitted dengue virus (DENV; family Flaviviridae, genus Orthoflavivirus, species Orthoflavivirus denguei) is a significant public health problem in many tropical and subtropical countries around the world. Human infection by DENV is predominantly asymptomatic in 80% of cases, but the remaining 20% of infections can result in symptoms ranging from a mild undifferentiated fever to life threatening dengue hemorrhagic and dengue shock syndrome. During infection DENV induces changes in the host cell, including changing protein expression, altering the cellular lipids and inducing changes in membrane architecture. A number of cell types have been shown to be permissive for DENV replication, including hepatocytes. This study sought to investigate the protein expression changes induced by DENV infection of a liver cell line, Huh-7, using 2-dimensional (2D) electrophoresis. At 48 hours post infection 14 protein spots were found to have altered expression as compared to mock infected cells at the same time point. In particular four of the proteins showing alterations of expression were chaperone proteins (Stress-70 protein, Endoplasmic reticulum chaperone BiP (GRP78), Heat shock 70 kDa protein 4 and Heat shock protein HSP 90-beta), of which three were upregulated (Stress-70 protein, Endoplasmic reticulum chaperone BiP (GRP78), Heat shock 70 kDa protein 4) and one was downregulated (Heat shock protein HSP 90-beta). GRP78 showed the largest change in expression amongst these four proteins, and so its expression was confirmed by western blot analysis. GRP78 has been shown by many studies to be critically involved in the replication of orthoflaviviruses, and this study further underlines the importance of this protein.